2015
DOI: 10.1371/journal.pone.0118340
|View full text |Cite
|
Sign up to set email alerts
|

How Does Anodal Transcranial Direct Current Stimulation of the Pain Neuromatrix Affect Brain Excitability and Pain Perception? A Randomised, Double-Blind, Sham-Control Study

Abstract: BackgroundIntegration of information between multiple cortical regions of the pain neuromatrix is thought to underpin pain modulation. Although altered processing in the primary motor (M1) and sensory (S1) cortices is implicated in separate studies, the simultaneous changes in and the relationship between these regions are unknown yet. The primary aim was to assess the effects of anodal transcranial direct current stimulation (a-tDCS) over superficial regions of the pain neuromatrix on M1 and S1 excitability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 102 publications
(122 reference statements)
4
76
0
Order By: Relevance
“…Previous studies have reported somewhat similar findings. While one study reported increases in FC between left DLPFC and bilateral primary sensorimotor cortices after tDCS (Stagg et al, 2013), another study reported significant increases in M1 corticospinal excitability (Vaseghi et al, 2015 Overall, our results demonstrate that both active M1 tDCS and active DLPFC tDCS modulate FC across sensory networks, although the influence of M1 tDCS appears to be more robust. Importantly, the validity of our findings is significant since FC effects of VPL were only modulated with active M1 and DLPFC tDCS, but not with sham.…”
Section: Fc Changes Across Sensory Networkmentioning
confidence: 41%
“…Previous studies have reported somewhat similar findings. While one study reported increases in FC between left DLPFC and bilateral primary sensorimotor cortices after tDCS (Stagg et al, 2013), another study reported significant increases in M1 corticospinal excitability (Vaseghi et al, 2015 Overall, our results demonstrate that both active M1 tDCS and active DLPFC tDCS modulate FC across sensory networks, although the influence of M1 tDCS appears to be more robust. Importantly, the validity of our findings is significant since FC effects of VPL were only modulated with active M1 and DLPFC tDCS, but not with sham.…”
Section: Fc Changes Across Sensory Networkmentioning
confidence: 41%
“…Walsh and Cummins (1976) suggested that the output latency to leave the first quadrant is a behavior associated with emotional factors, which may indicate an increase in anxiety-like behaviors (Stanford, 2007;Walsh and Cummins, 1976). Most importantly, tDCS treatment reverted those CCI-induced effects; therefore, we can suggest that this effect could have resulted from the action of tDCS on cortical areas involved in the pain matrix, such as the thalamus; anterior cingulate cortex (ACC); insular cortex; frontal, premotor, primary sensory and motor cortices (Moseley, 2003;Vaseghi et al, 2015;Zaghi et al, 2009). Additionally, previous studies from our group using chronic inflammation and hyperalgesia induced by chronic restraint stress models (Spezia Adachi et al, 2012) showed an antinociceptive effect of cortical stimulation by tDCS.…”
Section: Discussionmentioning
confidence: 99%
“…Although the primary motor cortex (M1) is not considered regularly as one of the pain neuromatrix, it plays a crucial role in modulating the pain in different chronic pain syndromes (25, 28, 35-37, 41, 45). It has some reciprocal connections with S1 (28, 37, 45).…”
Section: Methodsmentioning
confidence: 99%